1993
DOI: 10.1177/104225879301700404
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Alliances and Competitive Strategies in Small Manufacturing Firms

Abstract: This study extends existing work in the area of interorganizational relationships by exploring the interaction between the strategic posture of small firms and their propensity to form cooperative linkages. The most critical finding is that most small firms do use cooperative strategies, and that these strategies are used differentially by different strategic types. However, it is unclear whether there is a direct relationship between the competitive postures, interorganizational strategies, and small firm per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 18 publications
2
58
0
4
Order By: Relevance
“…A network can be broadly defined as "an integrated and co-ordinated set of ongoing economic and non-economic relations embedded within, among and outside business firms" (MacGregor, 2004, p. 65). It has been demonstrated that SMEs adopt particular network forms depending on their strategic orientation (Golden and Dollinger, 1993): prospectors, analyzers, and defenders are more likely to engage in confederate relationships, agglomerate/organic relationships, and conjugate relationships respectively. According to Jarratt (1998), confederate relationships refer to competitors with contractual agreements that synergize functional activities such as shared shipping costs, agglomerate relationships refer to competitors with no contractual arrangements such as trade organisations, organic relationships refer to traditional networking across industries such as board memberships or other voluntary organizations (indirect and non-contractual), and conjugate relationships refer to vertical linkages across the value chain such as buyer-supplier or subcontracting relationships.…”
Section: Strategic Orientation and Institutional Factorsmentioning
confidence: 99%
“…A network can be broadly defined as "an integrated and co-ordinated set of ongoing economic and non-economic relations embedded within, among and outside business firms" (MacGregor, 2004, p. 65). It has been demonstrated that SMEs adopt particular network forms depending on their strategic orientation (Golden and Dollinger, 1993): prospectors, analyzers, and defenders are more likely to engage in confederate relationships, agglomerate/organic relationships, and conjugate relationships respectively. According to Jarratt (1998), confederate relationships refer to competitors with contractual agreements that synergize functional activities such as shared shipping costs, agglomerate relationships refer to competitors with no contractual arrangements such as trade organisations, organic relationships refer to traditional networking across industries such as board memberships or other voluntary organizations (indirect and non-contractual), and conjugate relationships refer to vertical linkages across the value chain such as buyer-supplier or subcontracting relationships.…”
Section: Strategic Orientation and Institutional Factorsmentioning
confidence: 99%
“…La première, élaborée par des organisations qui cherchent à coordonner leurs efforts pour gérer collectivement un avenir incertain, consiste à ériger une protection collective face à une menace dans une logique défensive. Dans cette perspective, l'objectif serait de réduire l'incertitude (Golden et Dollinger, 1993). La seconde, consistant à s'associer pour saisir une nouvelle opportunité, renvoie à une logique plus proactive.…”
Section: Stratégies Collectives Et Parties Prenantesunclassified
“…In this study we use the network typology initially proposed by Astley and Formbrun (1983) that was integrated into the strategy literature by Dollinger (1990), Dollinger and Golden (1992), and Golden and Dollinger (1993) and then gave rise to a stream of studies in SME networking area (Alexander, 1998;Dana et al, 2000;Rao, 2002;Botti and Torres, 2008;Tsai and Lai, 2010). The major component of this typology is a distinction between symbiotic and non-symbiotic (commensal, commensalistic) networks.…”
Section: Symbiotic Type Of Networkingmentioning
confidence: 99%